Genesis of Permian granitoids in the southeast of Inner Mongolia and their response to the Xing’an-Mongolia orogenic belt evolution: constraints from zircon U-Pb age, geochemistry and Hf isotopes - Xue, Xiaogang; Zhang, Peng; Chen, Guoqiang; Zhang, Haihong; Zhang, Xuebin (Frontiers in Earth Science, 2024)
Research on the geological process of the Xing’an - Mongolia Orogenic Belt has attracted the attention of scholars both domestically and internationally. Its genesis and tectonic location may help revealing the geological processes asscoaited with the evolution of the Xing’an - Mongolia Orogenic Belt. This study focuses on the development of the Permian granitic complex in Jielin Ranch, and we conduct systematic geological, petrographic, zircon U-Pb chronology, Hf isotope, and geochemical tracing of rock elements for evidence. The results show that the granitic complex is mainly composed of monzogranite and syenogranite, which obtained zircon U-Pb ages of 291.1 ± 1.1 Ma and 260.8 ± 1.1 Ma, respectively. The monzogranite and syenogranite are all acidic and aluminum rich rocks, and the monzogranite is a potassium rich, high potassium calcium alkaline rock series with relatively low REE content, high degree of fractionation, and insignificant europium anomalies, enriched with LILE (Rb, Th, U, K), deficient elements such as Ba, Sr, Nb, Ti, and P, εHf(t) values are from +4.1 to +7.0 (TDM2=1130–920 Ma). Geochemistry shows that the monzogranite belongs to high fractionation of I-type granite, which formed in a subduction-compressional or extension tectonic environment, and Middle Neoproterozoic lower crust rocks as the major source material of magma. The syenogranite is a potassium high potassium transitional rock series with a high rare earth content (214 × 10−6∼325 × 10−6), low LREE/HREE (2.54–6.41), δEu (0.04–0.15) and the typical “four component effect” fractionation mode is enriched in large ion lithophilic elements such as Rb, Th, K, and strongly depleted in elements such as Ba, Sr, Nb, Ta, Ti, P, εHf(t) values are from +4.2 to +8.6 (TDM2=738–1228 Ma), suggesting the characteristics of an “A2 type” granite. The magma originated from partial melting of the lower crust of the Middle and Neoproterozoic with the participation of mantle derived melts, and was formed in a back-arc extensional environment. This suggests that the study area experienced a subduction-compressional or extension tectonic environment during the early Permian and a brief backarc extension process in the late Permian.